Effect of Material Hardness on Energy Dissipation From a Moving Crack in First Mode - Seyedmorteza Latifi (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
Fatigue crack growth is the reason of failure of mechanical parts under cyclic loading. When a crack forms in material a plastic zone surrounds the tip of the crack. In this paper, a model based on HRR singularity is utilized to find the strain energy dissipation from a crack tip. Material hardness effect on the dissipated strain energy is investigated. It is found that the strain energy dissipation decreases with hardness. The results also show the direct logarithmic relation between the stress intensity factor and strain energy dissipation of fatigue crack propagation.